POTENSI TEMPE PASTA STERIL IRADIASI SEBAGAI NUTRISI ENTERAL PASIEN YANG MENGGUNAKAN ALAT BANTU NASO GASTRIC TUBE (NGT) - Zubaidah Irawati; R. S. Adji Koesoemowidodo; Ades Puspita; Swasono R Tamat (Research Center for Chemistry - LIPI, 2013)
Food irradiation process has a potential topromote of a safe, adequate and nutritiousfood supply for hospital diets. It has twoapplications that can contribute to thehealth and well being of humanity, i.e. theelimination of foodborne pathogensmicroorganisms, and the preservation offoods by the destruction of pests. Effects ofionizing radiation on tempe pasta selectedas samples for patient food intake throughNaso Gastric Tube (NGT) has beenstudied. Tempe pasta was vacuum packedin a laminate pouch of po lyesteraluminumfoil- linear low densitypolyethylene and gamma irradiated atdoses of 10 kGy and 25 kGy , respectivelyunder cryogenic condition and then storedat room temperature for 6 and 12weeks. Some quality parameters wereobserved. There was no significantdifferences between un irradiated andirradiated tempe pasta on the moisturecontent, pH, protein content and viscosity.Meanwhile isojlavon genestein contentand antioxidant capacity showed anincrease by increasing irradiation dose upto 12 weeks of storage. Malonaldehydecontent in tempe pasta was accelerating byincreasing the irradiation dose andextending the storage period but Peroxidevalue was not detected in all treatedsamples. The irradiated tempe pasta atcertain degree of viscosity and particlesize could be considered as protein basefood intake for immunocompromisedpatients through Naso Gastric Tube(NGT).Keywords: Tempe pasta, food irradiation,isojlavon genestine, nutritious food,immunocompromised patients.